Simulation of Gas Sweetening Process using Extended NRTL and Stages Efficiency as Modeling Approach - Kurniawan, Aditya; Yusuf, Yusmardhany; Hazimizzufar, Ahnaf; Herviansyah, Wildan Zanuar (Program studi Teknik Kimia UNS, 2024)
Gas sweetening is a process to remove CO₂ and H₂S from natural gas. The current established technology is by using Amine contactor where the solvent used is in form of Amine solution. To simulate the effect of different solvent, electrolyte-NRTL is used to model the equilibrium, and mass transfer-kinetic is used to model the rate-based processes. This modeling approach is rather complex and available only in commercial and proprietary process simulation software. Therefore we propose an alternative modeling approach where we use extended NRTL and stage efficiency to model the acid gas absorption processes. We find that this approach is quite good to describe CO₂ absorption, yet unsuccessful to calculate the H₂S absorption. Inadequate vapor liquid equilibrium parameter regression for H₂S, specifically at low partial pressure might cause the problem. However the stage efficiency approach shows good result where it is comparable to rate-based model and corresponds to current understanding of physico-chemical phenomenon of acid gas absorption. Keywords:Gas sweetening, Unisim design, Simulation, NRTL, Stage efficiency